2017
DOI: 10.22202/tus.2016.v2i2.1316
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Reading Comprehension Achievement at the Eighth Grade Students of SMP Muhammadiyah 1 Rawa Bening By Using DRTA and KWL Strategies

Abstract: The Influence of Reading Comprehension Achievement at the Eighth Grade Students of SMP Muhammadiyah 1 Rawa Bening By Using DRTA and KWL Strategies

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Teaching English reading in Indonesia is to develop comprehension skills. According to Andriani (2016), comprehension is the main goal of reading. Reading activities in secondary classrooms typically focused on searching for main ideas, learning new vocabulary, and emphasising grammatical structure (Lie, 2007;Madya, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Teaching English reading in Indonesia is to develop comprehension skills. According to Andriani (2016), comprehension is the main goal of reading. Reading activities in secondary classrooms typically focused on searching for main ideas, learning new vocabulary, and emphasising grammatical structure (Lie, 2007;Madya, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…
Teaching English reading in Indonesia is to develop comprehension skills. According to Andriani (2016), comprehension is the main goal of reading. In this study, the researcher wants to find out whether Directed Reading-Thinking Activity (DRTA) is a strategy that can guide students in asking questions about a text, making predictions, and then reading to confirm or refute their predictions to achieve the good and enhanced comprehension.
…”
mentioning
confidence: 99%
“…These skills are critical in understanding a text. Lastly, it makes reading more interesting and motivating hence facilitating comprehension [3], [25].…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of DRTA strategy has been investigated in some researches on distinctive contexts and scopes, e.g. (Augustine, Suparman, & Mahpul, 2019;Andriani, 2017;Faisal & Lova, 2018;Hasanah, 2016;Lubis, 2018;Sari, 2017). According to Augustine et al, (2019) DRTA was the three stages of comprehension: questioning, predicting, and confirming or refuting, in order to assist student for reading.…”
Section: Introductionmentioning
confidence: 99%
“…According to Augustine et al, (2019) DRTA was the three stages of comprehension: questioning, predicting, and confirming or refuting, in order to assist student for reading. In addition, Andriani (2017) revealed that the purpose of DRTA was fostering students to be considerate and critical reader. Meanwhile, Sari (2017) argued that the activity in DRTA also can assist students to comprehend the text by breaking the segment and predicting the next.…”
Section: Introductionmentioning
confidence: 99%